Sharih and Kinayah Expressions in Scriptural Texts: An Analysis of Meaning, Application, and Their Legal Implications in Usul al-Fiqh - Annisa Fausya; Fatmawati F; Muh. Nur Taufiq Sunusi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Within the field of Ushul Fiqh, the notions of lafaz sharih (explicit expression) and lafaz kinayah (implicit expression) serve as crucial tools in the derivation of Islamic law. A sharih statement is regarded as explicit, unambiguous, and limited to a single meaning, thus generating legal consequences automatically without the need for supporting evidence such as intention or contextual clues. Conversely, kinayah refers to indirect or ambiguous language that may invite multiple interpretations, making its legal application contingent upon the speaker’s intention and surrounding context. Classical jurists, including al-Ghazali, al-Amidi, Ibn Qudamah, and al-Syathibi, underscored this distinction by classifying sharih as qath’i al-dilalah (definitive in indication) and kinayah as zanni al-dilalah (probabilistic in indication). Using a descriptive-analytical framework and library-based research, this study examines both traditional sources and modern contributions. The analysis demonstrates that the distinction between sharih and kinayah plays a pivotal role in various domains such as family law—particularly divorce and marriage contracts—commercial agreements, and the interpretation of Qur’anic and Hadith texts. Furthermore, while kinayah is often preferred for its politeness in communication, sharih provides greater legal certainty. This divergence influences the scope of ijtihad and the ethical dimension of social interactions.